Hadis Tentang Wanita Menjadi Pemimpin: Menelisik Antara Pemahaman Tekstual dan Kontekstual Perspektif M. Syuhudi Ismail - Ummi Kalsum Hasibuan; Hafizzullah Hafizzullah (UIN Sunan Gunung Djati Bandung, 2021)
This paper examines the hadith about women becoming leaders from a textual and contextual perspective M. Syuhudi Ismail. This shows that the hadith should not always be understood merely textually, but rather by paying attention to the socio-historical and context of the hadith. The purpose of this paper is to uncover and know about how the understanding of women's traditions becomes a leader in the textual and contextual review of Shuhudi. The approach used is a descriptive-analysis approach. The results of this study are: first, the textual hadith of the appointment of women as leaders is prohibited and at that time women did not have authority at all. Second, the contextual understanding of the hadith of women becoming leaders changes with time as time goes by. So that in this context Syuhudi's contextual understanding is that women may become leaders on the condition that they have authority, are able to lead and society accepts if women are leaders. In this case Syuhudi did it by looking at an analysis of asbab al-wurud and the macro context in the Persian region. Third, M. Syuhudi Ismail classifies the traditions of women into leaders as traditions related to the current situation (developing). Therefore the hadith must be understood contextually, because the contents of the hadith instructions are temporal.